The emergence of biological problems in electronic school books (bse) class x reviewed from the scientific knowledge domain of scientific literacy - Aa Juhanda; Yoga Maryanto (Biosfer: Jurnal Pendidikan Biologi, 2018)
This descriptive study was conducted with the aim to determine the emergence of biological problems in class XE in terms of the scientific knowledge domain of scientific literacy covering aspects of content/content, procedural and epistemic. The sample of this study consisted of 295 questions contained in the 2009 edition of BSE Biology Class X book, determined by purposive sampling technique which included examples of questions and exercises. The instrument used in this study is a document analysis document about the domain of scientific knowledge of scientific literacy. The results of the problem analysis showed that the aspect of content had the highest percentage appearance of 85.42% (excellent category) compared to the procedural aspects of 9.83% (very poor) and epistemic aspects of 1.36% (less). Based on these results it can be concluded that the domains of scientific literacy scientific knowledge contained in the class X BSE book are not balanced evenly so that the distribution of the question needs to be rearranged.